OBTAINING AND EFFICIENT USE OF HYDROPHOBIC THERMAL INSULATION MATERIALS BASED ON MODIFIED LIQUID GLASS IN CONSTRUCTION - Imamov Sukhrob Solexovich (Web of Journals Publishing, 2025)
This study explores the acquisition and efficient application of hydrophobic thermal insulation materials based on modified liquid glass in the construction industry. The research focuses on enhancing the thermal insulating properties of liquid glass through chemical modifications, resulting in materials that offer superior moisture resistance, improved thermal conductivity, and long-lasting durability. By integrating hydrophobic characteristics into the insulation, the materials not only prevent water absorption but also maintain their insulating efficiency under varying environmental conditions. The study also examines the production methods, cost-effectiveness, and practical application of these materials in building construction, aiming to contribute to energy-efficient, sustainable, and environmentally friendly building practices. The findings highlight the potential of modified liquid glass as a promising solution for improving energy performance in modern construction.
Keywords: Hydrophobic materials, Thermal insulation, Liquid glass, Modified liquid glass, Construction materials, Building insulation, Sustainable construction, Building envelope, Energy-saving materials.